Pengaruh Interaksi Guru dan Siswa dalam Pembelajaran dan Fasilitas Belajar Terhadap Prestasi Belajar Ekonomi Pada Siswa Kelas XI IPS SMA Negeri 3 Klaten Tahun Ajaran 2014/2015 - Meilani, Meilani (2016)
The purpose of this study to determine the effect of: 1) the interaction of teachers and students in learning the learning achievement of economic, 2) learning facilities on the learning achievement of economic, 3) Interaction of teachers and students in teaching and learning facilities to the achievement of economic study. This research is quantitative research associative. The population in this study were students of class XI IPS SMAN 3 Klaten amounted to 95 students and the sample in this study is 75 students. The necessary data, obtained through questionnaire method and the method of documentation. Previous questionnaire has been tested with validity and reliability. The analysis technique used is multiple linear regression, t test, F test, Effective and Relative contribution. Results showed regression equation Y = 35.828 + 0,399X1 + 0,337X2 means that the interaction of teachers and students in teaching and learning facilities positive effect on the learning achievement of the economy. Conclusion: 1) there is an interaction effect of teachers and students in the learning of learning achievement economy. Based on test results obtained t t> t table, namely 7.007> 1,993 (α = 5%) and a significance value <0.05, namely 0.000. 2) no effect on the learning achievement of learning facilities economy. Based on test results obtained t t> t table, namely 5,270> 1,993 (α = 5%) and a significance value <0.05, namely 0.000. 3) there is an interaction effect of teachers and students in teaching and learning facilities for interpretation studying economics. Based on test results obtained value F Fhitung> Ftable is 55.512> 3.12 and a significance value <0.05, namely 0.000. 4) The variable interaction of teachers and students in learning contribute effectively by 37%, variable learning facilities provide effective contribution of 23.7%, total effective contribution amounted to 60.7%, so it can be said that the interaction of teachers and students in learning more dominant affect learning achievement. 5) The result of the coefficient of determination (R2) of 0.607 indicates that the influence of the interaction of teachers and students in teaching and learning facilities to the achievement of economic study was 60.7% with the remaining 39.3% is influenced by other variables that are not investigated by researchers.